Barriers to women’s economic empowerment in Iraq - Shamy, Dr. Salam Al; Abbas, Marwa Abdel Rahim (The journal of contemporary issues in business and government, 2021)
There is small percentage of women in labor force in Iraq, despite their high proportion of the population. The matter explains this phenomena is the nature of the rentier economy and neglecting of state institutions as a whole to create a work environment ready to motivate and encourage women in different their lives stages on paid work and continue to do by their whole activity. This ratio of productivity work force declines and enhances the role of Iraqi oil sector in economy movement resulted in creation weak economy depends on increases or decreases of growth rate occurs in oil revenues, in other words on the fluctuations in global oil prices. To get rid of the consumption pattern of population over the age of 15 at the expense of style production distinguishes developing countries in general and Iraq in particular, there is a set of procedures operating on optimum utilization of human capital contribute to change the course of the economy towards sustainable development requirements of justice in the distribution of income and achievement high savings rates also investment product for new job opportunities while maintaining the ability of future generations to achieve development. One of these procedures enacting laws, amending and cancelling other laws, commensurate with achieving increasing the productivity of the bulk of the workforce goal besides the use of the budget gender-sensitive and public procurement policies to eliminate unequal access to economic resources between males and females.